Monsters, desire and the creative queer body. Issue 5 (2nd September 2016) - Jones, Stacy Holman; Harris, Anne
Abstract: In this essay, we return to the queer potential of the monstrous and extend it to the 'invisibility' and unintelligibility of non-binary trans* gender subjectivities and femme sexuality. In a text that moves between performative and expository prose – between two voices who speak to the rage, pride, and pleasure of monstrously queer gender identifications and sexualities – we write the power of being seen but not understood, of passing unnoticed, of subverting sexual and gender fixities. Like Mary Shelley's Frankenstein, the monstrous is both a construction, a figure who signifies selves and ways of living the world cannot 'bear to see', and a narrative 'form of unleashing', a way of writing ourselves out of the 'bind' of gender binaries, heteronormative desires and traditional forms of kinship.